Ethnomedicinal Uses, Phytochemistry, and Anticancer Potentials of African Medicinal Fruits: A Comprehensive Review - Nosipho Thembekile Fakudze; Paromita Sarbadhikary; Blassan P. George; Heidi Abrahamse (MDPI AG, 2023)
Africa is home to diverse medicinal plants that have been used for generations for the treatment of several different cancers and, presently, they are gaining interest from researchers as promising approaches to cancer treatment. This review aims to provide a comprehensive review of dietary and medicinal African fruits including their traditional uses, botanical description, ethnobotanical uses, bioactive phytochemical compositions, and anticancer properties investigated to date in vitro, in vivo, and in clinical studies. Data on recent updates concerning the traditional uses and anticancer properties of these fruits were collected from a myriad of available publications in electronic databases, such as Web of Science, PubMed, ScienceDirect, Scopus, SpringerLink, and Google Scholar. The results suggest that approximately 12 native or commercially grown African fruits belonging to different plant species, including Tribulus terrestris, Xanthium strumarium, Withania somnifera, Xylopia aethiopica, Abelmoschus esculentus, Carissa macrocarpa, Carpobrotus edulis, Syzygium cumini, Kigelia Africana, Annona muricata, Persea americana, and Punica granatum, have been reported for their potential as treatment options for the management of cancer. We further found that approximately eight different fruits from native plant species from Africa, namely, Sclerocarya birrea, Dovyalis caffra, Parinari curatellifolia, Mimusops caffra, Carpobrotus edulis, Vangueria infausta, Harpephyllum caffrum, and Carissa macrocarpa, have been widely used for the traditional treatment of different ailments but somehow failed to gain the interest of researchers for their use in anticancer research. In this review, we show the potential use of various fruits as anticancer agents, such as Tribulus terrestris, Xanthium strumarium, Withania somnifera, Xylopia aethiopica, Abelmoschus esculentus, Carissa macrocarpa, Carpobrotus edulis, Syzygium cumini, Kigelia Africana, Annona muricata, Persea americana, and Punica granatum; unfortunately, not enough reported research data have been published to gain thorough mechanistic insights and clinical applications. Additionally, we discuss the possibility of the utilization of potential phytochemicals from fruits like Persea americana and Punica granatum in anticancer research, as well as future directions.